Contrôle et manipulation au cœur de la firme-monde ? - Virgile Chassagnon (Revue de la Régulation)
The aim of this contribution is to question the nature of the power relationships that characterize the governance regime of big modern firms, here called “world-firms”. The originality of this paper is double. On one hand, after having defined what a world-firm is it aims at combining in a same analysis a reflection on the internal governance (employment relationship) and a reflection on the external governance of the world-firms (international subcontracting relationships) by using a particular lens : power. On other hand, it proposes to develop a new concept, namely the one of “controlation” (which is the neologism of control and manipulation), to portray the complexity and subtlety of the governance regimes of these firms that are based on both a fragmentation and a subversion of the regulating boundaries of the industrial capitalism.